Cointegration between macroeconomic factors and the exchange rate USD/CNY - Muhammad Kamran Khan; Jian-Zhou Teng; Muhammad Imran Khan (Financial Innovation, 2019)
This research paper investigates the effect of macroeconomic variables on the exchange rate USD/CYN using yearly time series data for China economy from 1980 to 2017. ARDL bounds test approach for cointegration is applied to test the long-run relation between the dependent and the independent variables. The results of long-run ARDL indicate that gross domestic product growth and trade openness have a positive effect on the exchange rate USD/CNY while interest and inflation rates have a negative effect on the exchange rate. Based on the results of this study, it is recommended that the policymakers of the Chinese government should implement vital monetary and fiscal policies to determine the less volatile and productive exchange rate for China to manage sustainable economic growth for a long time with its trading partners.
Keywords: F62; F31; C22; 650; Exchange rate; Macroeconomic factors; ARDL